The Relationship Between Sitting Duration While Working in the Office With Complaints of Lower Back Pain in General Administration at Saiful Anwar Hospital Malang - Melur Belinda; Amin Zakaria; Wiek Israwan; Fransisca Xaveria Hargiani (Universitas Muhammadiyah Malang, 2022)
Administration officer is a profession that sits for a long duration, working on a computer device. Sitting for a long time can cause low back pain. Low back pain is one of the diseases that can cause disability and disorders. This disease can reduce effectiveness in work. This pain arises from a long sitting position causing continuous spasms on muscle. Research Objective: Knowing the relationship between sitting duration while working with lower back pain in administration officers. Research Method: This study used Cross-Sectional research methods with a total sample in this study of 202 people. Sample were given Rolland Morris questionnaires and responded directly. The data was analyzed using Chi-Square Test. Results: 16.7% of people with a long sitting duration <4 hours had complaints of low back pain, and as many as 48% of respondents with a working duration of > 4 hours had complaints of back pain. Statistical test results using the Chi-Square Test obtained a p = 0.026 < 0.05. Thus it can be concluded that there is a long-standing relationship of sitting with complaints of low back pain in Administration officer of Saiful Anwar Malang Hospital. Conclusion: Long sitting duration done for several years can cause disorders in the body. The working period causes a continuous static load, and workers who ignore ergonomic factors can cause low back pain.